Electrocardiographic screening in athletes: the time is now for universal screening - Papadakis, M.; Sharma, S. (British Journal of Sports Medicine, 2009)
Regular physical exercise reduces cardiovascular morbidity and mortality. A small proportion of athletes, however, are at increased risk of exercise-related sudden cardiac death (SCD) as a result of quiescent cardiac anomalies. The preventable nature of such deaths has prompted the medical and sporting governing bodies to recommend preparticipation cardiovascular screening (PPS) in young athletes (<=35 years) to permit the identification of potentially fatal disorders. Although evidence from the Italian experience suggests that electrocardiographic screening of young athletes has led to a significant reduction in SCD from cardiomyopathies, considerable controversy relating to the efficacy, cost-effectiveness and the impact of false-positive results of PPS still exists. This review presents an appraisal of all the available scientific evidence, attempting to resolve the concerns of the antagonists and examine how PPS compares with the World Health Organization screening criteria, providing compelling justifications for the implementation of universal PPS in young, competitive athletes.